Factors associated with Chronic Obstructive Pulmonary Disease burden in India - Manas Pratim Roy (Wolters Kluwer Medknow Publications, 2021)
OBJECTIVE: Chronic Obstructive Pulmonary Disease (COPD) is the second major contributor to disease burden in India, courtesy to tobacco use, and air pollution. However, there are not many studies with a nationwide approach. The present paper aims to correlate Disability-Adjusted Life Years (DALY) due to COPD with tobacco use, secondhand smoking, the use of clean fuel, and economic condition. MATERIALS AND METHODS: The study adopted an ecological approach. A secondary analysis was carried out on data collected from the National Family Health Survey 4, the Global Adult Tobacco Survey 2: India 2016-17, and India: Health of the Nation's States. Spearman correlation coefficient and multivariate linear regression were used for state-wise analysis. RESULTS: It was found that states with higher COPD burden were confined to North India. Smoking and secondhand smoking had positive relationships with COPD burden. On regression, smokeless tobacco (SLT) was significantly associated with DALY due to COPD. CONCLUSION: States with the highest proportion of SLT need special intervention to reduce COPD burden in the country.